2020
DOI: 10.1371/journal.pone.0238246
|View full text |Cite
|
Sign up to set email alerts
|

Development of global visual processing: From the retina to the perceptive field

Abstract: Young children exhibit poorer visual performance than adults due to immaturity of the fovea and of the fundamental processing of visual functions such as masking and crowding. Recent studies suggest that masking and crowding are closely related to the size of the fundamental processing unit—the perceptive field (PF). However, while it is known that the retina and basic visual functions develop throughout childhood, it is not clear whether and how changes in the size of the PF affect masking and crowding. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…No binocular advantage of the threshold elevations was found, confirming recent findings that sometimes two eyes are not better than one in cases of contextual modulations 76 , 77 , 79 . In light of our results, and since (1) both crowding and masking are dependent on the perceptual field size 48 , 59 , 102 , 112 and (2) crowding is similar to lateral interactions in certain spatial and temporal conditions 48 , we suggest that heterophoria could affect the symmetry of the perceptive field as well as the crowding effect—a hypothesis that deserves further investigation.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…No binocular advantage of the threshold elevations was found, confirming recent findings that sometimes two eyes are not better than one in cases of contextual modulations 76 , 77 , 79 . In light of our results, and since (1) both crowding and masking are dependent on the perceptual field size 48 , 59 , 102 , 112 and (2) crowding is similar to lateral interactions in certain spatial and temporal conditions 48 , we suggest that heterophoria could affect the symmetry of the perceptive field as well as the crowding effect—a hypothesis that deserves further investigation.…”
Section: Discussionmentioning
confidence: 50%
“…It was suggested that the suppressive zone is indicative of the perceptive field size (the perceptive field is the psychophysical analog to the classical receptive field in the visual cortex, for a review, see 48 , 105 , 106 ). Recently, it was shown that the binocular perceptive field size decreases with development, reaching an adult’s size in up to 5–6 years 59 ; however, these findings did not determine whether the perceptive field size would be different between the horizontal and the vertical meridian in general, and in heterophoria, in particular.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The estimated size of the PF in this method is in agreement with previous studies using different methods. This method is used to estimate the development of collinear facilitation in children; it is related to the PF’s size 57 ; hence, it is the method that we chose for estimating the PF’s size in this study. We compared the estimation of the PF obtained using two types of lateral masking paradigms: the classic LM featuring flankers with an equal phase to the target, and the LM used by Zenger and Sagi 49 featuring opposite-phase flankers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the PF’s size can also be modified by perceptual learning 70 72 or by its development. Recently, it was shown that the binocular perceptive field size decreases with development, reaching an adult’s size in up to 5–6 years 57 . In amblyopia, a pathology resulting from the absence of correlated binocular vision experience during the critical period at about 6 years old, it was shown that the PF’s size was greater than in neurotypical subjects, regardless of the amblyopia type (anisometropic or strabismic) 73 , 74 .…”
Section: Introductionmentioning
confidence: 99%